Processes controlling the distributions and cycling of dissolved aluminum and manganese in the northeastern Indian Ocean - Yang, Yichao; Li, Lei; Ren, Jingling; Jiang, Shuo; Zhang, Jing (Frontiers in Marine Science, 2023)
Aluminium and Manganese are both key parameters in the GEOTRACES program. Data on dissolved aluminium (dAl) and dissolved manganese (dMn) relative to their geochemical behaviour remains limited in the northeastern Indian Ocean (IO, including Bay of Bengal (BoB) and equatorial Indian Ocean (Eq. IO)). Seawater samples collected in the BoB and Eq. IO during the spring inter-monsoon period (7th March to 9th April) of 2017 were analysed to investigate the behaviour and main processes controlling the distributions of dAl and dMn in the northeastern IO. The average concentrations of dAl and dMn in the mixed layer of BoB were 16.6 nM and 6.7 nM, respectively. A modified 1-D box-model equation was utilized to estimate the contributions of different sources to dAl and dMn in the mixed layer. Al released from the desorption of and/ or dissolution of the lithogenic sediments discharged by the Ganga-Brahmaputra (G-B) river system, predominantly controlled the dAl distributions in the mixed layer of BoB. While the desorption from the lithogenic sediments only contributed about 13% 21% dMn. Additional dMn input from the advection of Andaman Sea water and photo-reduction-dissolution of particulate Mn (IV) contributed more than 60% dMn in the mixed layer of BoB. dAl and dMn in the surface mixed layer of Eq. IO were mainly affected by the mixing of dAl and dMn enriched BoB surface water and low-dAl, low-dMn southern Arabian Sea surface water. Considering water mass properties and dAl concentrations, the distributions of dAl in the intermediate water (750 1500 m) of northeastern IO were controlled by the mixing of Red Sea Intermediate Water, Indonesian Intermediate Water, and intermediate water of BoB. Different with dAl, the apparent oxygen utilization relationship with dMn concentrations indicated that the regeneration of lithogenic particles under hypoxic condition played a more important role than remineralization of settling organic particles in controlling dMn distributions in the subsurface and intermediate water body (100 1000 m) of BoB, and that remineralization of biogenic particles mattered to dMn in the subsurface of Eq. IO.